An overview of functionalised carbon nanomaterial for organic pollutant removal - Jun, L.; Mujawar, Mubarak; Yee, M.; Yon, L.; Bing, C.; Khalid, M.; Abdullah, E. (Elsevier, 2018)
Carbon nanomaterials (CNMs), particularly carbon nanotube and graphene-based materials, are rapidly emerging as one of the most effective adsorbents for wastewater treatment. CNMs hold great potential as new generation adsorbents due to their high surface to volume ratio, as well as extraordinary chemical, mechanical and thermal stabilities. However, implementation of pristine CNMs in real world applications are still hindered due to their poor solubility in most solvents. Hence, surface modification of CNMs is essential for wastewater treatment application in order to improve its solubility, chemical stability, fouling resistance and efficiency. Numerous studies have reported the applications of functionalized CNMs as very promising adsorbents for treating organic and inorganic wastewater pollutants. In this paper, the removal of organic dye and phenol contaminants from wastewater using various type of functionalized CNMs are highlighted and summarized. Challenges and future opportunities for application of these CNMs as adsorbents in sustainable wastewater treatment are also addressed in this paper.